Preparation method and application of copper nanoparticles with controllable size and crystal face
The preparation of copper nanoparticles with controllable size and crystal surfaces through ultrasonic and electrochemical reduction methods has solved the problem of poor selectivity and insufficient stability in the electrocatalytic reduction of carbon dioxide by existing copper-based catalysts, and achieved efficient ethylene catalytic activity and Current density simplifies the preparation process.
Patent Information
- Application Number
- CN202411503523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing copper-based catalysts have problems such as poor selectivity, slow electron-to-movement mechanics, small current density and poor stability in the process of electrocatalytic reduction of carbon dioxide. The existing preparation methods are complex in the process and high equipment requirements, making it difficult to control the catalyst at the same time. size and crystal surface.
Using commercial copper powder as a precursor, copper nanoparticles with controllable size and crystal surfaces are prepared through ultrasonic and electrochemical reduction methods. Ultrasonic treatment is used to regulate the size of nanoparticles, and their crystal surfaces are regulated through electrochemical reduction to form suitable catalyst.
The excellent performance of copper nanoparticles in electrocatalytic reduction of carbon dioxide reaction is achieved, the catalytic activity and current density of ethylene is improved, the maximum Faraday efficiency reaches 80%, and the partial current density can reach 1.1A cm-2, simplifying the preparation process and reducing Raw material requirements.
Smart Images

Figure CN119243221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanoparticle preparation, and specifically relates to a method for converting copper powder into copper nanoparticles with controllable size and crystal surface, and application of the method in the field of electrocatalytic reduction of carbon dioxide. Background Art
[0002] Due to deforestation and over-exploitation of fossil fuels during the Industrial Revolution, the concentration of carbon dioxide in the atmosphere has risen from 277ppm to today's record high of more than 400ppm. It is expected that by 2100, the value will reach 600ppm, greatly exceeding the safety threshold of 350ppm and causing serious environmental problems such as global warming, desertification and species extinction. Therefore, in order to overcome the greenhouse effect, people have invested a lot of energy in developing different carbon dioxide conversion technologies. Researchers have developed various methods (e.g., biological, thermochemical, electrochemical and photochemical conversions) to use carbon dioxide as a carbon source to electrochemically synthesize high-value fuels / chemicals (e.g., CO, CH4, HCOOH, C2H4 and C2H5OH). At the same time, the synthesis of carbon products by electrochemical CO2 reduction (ECR) has also aroused great interest among researchers because it can achieve CO2 electrosynthesis by integrating electricity generated by renewable energy (such as solar, wind and tidal energy) at ambient temperature and pressure in modular, compact, flexible and scalable devices.
[0003] Copper catalysts for electroreduction of carbon dioxide to produce hydrocarbons and C 2+ The unique properties of oxygen-containing compounds are that the adsorption energy of the intermediate *CO is negative and the adsorption energy of *H is positive, so it tends to reduce CO2 to hydrocarbons and alcohols, which has attracted scientists to study for decades. At present, when using copper-based catalysts, CO2 electroreduction can be achieved at current densities as high as 1A cm -2 Electrochemical synthesis of C 2+ However, the use of Cu catalysts for ECR still has many challenges, such as poor selectivity, slow electron transfer kinetics, small current density, and poor stability.
[0004] The size and shape of the material directly determine the number of active sites of the electrocatalyst in ECR. Existing studies generally believe that the smaller the size of the catalyst, the more active sites it will expose during the reaction. Therefore, smaller electrocatalysts usually exhibit better catalytic activity. In addition to size regulation, controlling various metal nanostructures and shapes to regulate the active sites and specific crystal faces exposed during the catalytic process is another effective means to regulate catalytic activity. For example, in copper catalysts, the exposure of different crystal faces during the reaction process directly affects the catalytic selectivity. When the exposed crystal face is the (111) crystal face, the main catalytic product is CH4, and when the exposed crystal face is the (100) crystal face, the main catalytic product is converted into C2H4.
[0005] The copper-based materials used for electrocatalytic reduction of carbon dioxide are mainly single copper, copper oxide, cuprous oxide or alloy materials containing copper components. The raw materials used in the current methods for preparing copper-based catalysts are mostly metal salts containing copper elements or copper-containing templates, which will produce large pollution during the reaction process. In addition, most of the current methods for preparing copper-based materials require the participation of precipitants such as sodium hydroxide and urea. The reaction process is complex and changeable, the reaction conditions are relatively harsh, the equipment requirements are relatively strict, and the prepared catalyst materials cannot achieve the effect of simultaneously controlling the size and crystal surface.
[0006] In summary, most of the existing methods for preparing copper-based materials have complex processes or high requirements on equipment and raw materials. Summary of the invention
[0007] In view of the shortcomings of the above-mentioned existing preparation methods, the present invention provides a method for preparing copper nanoparticles with controllable size and crystal surface, aiming to make them have excellent performance in electrocatalytic reduction of carbon dioxide to produce ethylene.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing copper nanoparticles with controllable size and crystal plane, characterized in that commercial copper powder is used as a precursor, and the commercial copper powder can be converted into copper nanoparticles with controllable size and crystal plane through ultrasonic and electrochemical reduction. The specific method is:
[0010] The commercial copper powder is dispersed in an ultrasonic solution to form a dispersion; the obtained dispersion is subjected to ultrasonic treatment, and the sample after the ultrasonic treatment is collected to obtain copper nanoparticles of a desired size; and then the obtained nanoparticles are subjected to electrochemical reduction treatment to obtain copper nanoparticles with a desired crystal surface.
[0011] Furthermore, the ultrasonic power is 400W and the ultrasonic time is 8 to 20 hours.
[0012] Furthermore, the potential of the electrochemical reduction is (-0.1) to (-1.0) V vs. RHE, and the reduction time is 0 to 40 min.
[0013] Furthermore, the usage ratio of the commercial copper powder to the ultrasonic solution is 0.1-1000 mg:100 mL.
[0014] Furthermore, the ultrasonic solution is a mixture of one or more liquids selected from N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), isopropyl alcohol (IPA), ethanol and water.
[0015] Compared with the existing technology, the beneficial effects of the present invention are embodied in:
[0016] 1. Compared with the previous method for preparing copper nanoparticles, the method mentioned in the present invention adjusts the size of copper nanoparticles by controlling the ultrasonic time. Copper nanoparticles of different sizes expose different crystal planes after electrochemical reduction, thereby achieving simultaneous control of size and crystal plane.
[0017] 2. The copper nanoparticles prepared by the present invention can be used as catalysts in the electrocatalytic reduction of carbon dioxide, and have excellent performance. The catalytic activity of producing ethylene is very high. The maximum Faraday efficiency of commercial copper powder to produce ethylene is only 24%, and the current density of the ethylene part is only ~0.023A cm -2 The maximum Faraday efficiency of the copper nanoparticles prepared by the present invention for producing ethylene can reach 80%, and the partial current density of ethylene can reach ~1.1A cm -2 .
[0018] 3. The present invention provides a novel method for preparing copper nanoparticles with controllable size and crystal plane, which can directly convert commercial copper powder into copper nanoparticles with controllable size and crystal plane. The raw material source is wide and the method is simple, which provides a new idea for the subsequent preparation of copper nanoparticles with different sizes and crystal planes. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the SEM image of the commercial copper powder used in Example 1 ( Figure 1 (a)) and the TEM image, HRTEM image and particle size distribution image of the prepared copper nanoparticles ( Figure 1 (b,c,d) in the figure.
[0020] Figure 2 This is the SEM image of the commercial copper powder used in Example 2 ( Figure 2 (a)) and the TEM image, HRTEM image and particle size distribution image of the prepared copper nanoparticles ( Figure 2 (b,c,d) in the figure.
[0021] Figure 3 This is the SEM image of the commercial copper powder used in Example 3 ( Figure 3 (a)) and the TEM image, HRTEM image and particle size distribution image of the prepared copper nanoparticles ( Figure 3 (b,c,d) in the figure.
[0022] Figure 4 This is the SEM image of the commercial copper powder used in Example 4 ( Figure 4 (a)) and the TEM image, HRTEM image and particle size distribution image of the prepared copper nanoparticles ( Figure 4 (b,c,d) in the figure.
[0023] Figure 5 This is the SEM image of the commercial copper powder used in Example 5 ( Figure 5 (a)) and the TEM image, HRTEM image and particle size distribution image of the prepared copper nanoparticles ( Figure 5 (b,c,d) in the figure.
[0024] Figure 6 The product efficiency distribution diagram and current diagram of the electrocatalytic reduction of carbon dioxide by the commercial copper powder used in each example.
[0025] Figure 7 (a) to (d) are the product efficiency distribution diagrams and current diagrams of the electrocatalytic reduction of carbon dioxide by the copper nanoparticles prepared in Examples 1-4, respectively.
[0026] Figure 8 (a) to (d) are respectively diagrams of the adsorption state of *CO intermediates on the surface of the copper nanoparticles prepared in Examples 1-4 during the electrocatalytic reduction process. DETAILED DESCRIPTION
[0027] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings and embodiments.
[0028] The ultrasonic solution used in the following examples is a mixed solution of isopropanol and water in a volume ratio of 1:1.
[0029] The electrochemical reduction method in the following embodiment is as follows: first, the prepared catalyst powder is weighed, and then dispersed in a mixed solution of isopropanol and water (volume ratio 3:1) to form a dispersion, and then the dispersion is ultrasonically homogenized to obtain a catalyst slurry. The catalyst slurry is sprayed onto carbon paper by air spraying to obtain a catalyst electrode, and then the prepared catalyst electrode is used as a working electrode, the Ag / AgCl electrode is used as a reference electrode, and the nickel mesh is used as a counter electrode. A three-electrode electrochemical reduction is performed using a constant potential method, and the electrolyte is 1 molL -1 of potassium hydroxide solution.
[0030] Example 1
[0031] In this example, commercial copper powder is used as raw material to prepare copper nanoparticles. The specific steps are as follows:
[0032] Weigh 1 g of commercial copper powder and disperse the weighed copper powder in 200 mL of ultrasonic solution to form a dispersion. The obtained dispersion is ultrasonicated at a power of 400 W for 8 h, and the ultrasonically treated sample is collected. The collected sample is electrochemically reduced at a potential of -1.0 V vs. RHE to obtain copper nanoparticles of corresponding size and crystal surface.
[0033] The SEM image of the commercial copper powder used in this example is as follows: Figure 1 (a) shows the TEM image, HRTEM image and particle size distribution of the prepared copper nanoparticles. Figure 1 As shown in (b, c, d), it can be seen that the product is copper nanoparticles with a particle size of 50 nm and exposed (111) crystal plane.
[0034] Example 2
[0035] In this example, commercial copper powder is used as raw material to prepare copper nanoparticles. The specific steps are as follows:
[0036] Weigh 1 g of commercial copper powder and disperse the weighed copper powder in 200 mL of ultrasonic solution to form a dispersion. The obtained dispersion is ultrasonicated at a power of 400 W for 12 h, and the ultrasonically treated sample is collected. The collected sample is electrochemically reduced at a potential of -1.0 V vs. RHE to obtain copper nanoparticles of corresponding size and crystal surface.
[0037] The SEM image of the commercial copper powder used in this example is as follows: Figure 2 (a) shows the TEM image, HRTEM image and particle size distribution of the prepared copper nanoparticles. Figure 2 As shown in (b, c, d), it can be seen that the product is copper nanoparticles with a particle size of 25 nm and exposed (111) crystal plane.
[0038] Example 3
[0039] In this embodiment, commercial copper powder is used as raw material to prepare copper nanoparticles. The specific steps are as follows:
[0040] Weigh 1 g of commercial copper powder and disperse the weighed copper powder in 200 mL of ultrasonic solution to form a dispersion. The obtained dispersion is ultrasonicated at a power of 400 W for 16 h, and the ultrasonically treated sample is collected. The collected sample is electrochemically reduced at a potential of -1.0 V vs. RHE to obtain copper nanoparticles of corresponding size and crystal surface.
[0041] The SEM image of the commercial copper powder used in this example is as follows: Figure 3 (a) shows the TEM image, HRTEM image and particle size distribution of the prepared copper nanoparticles. Figure 3 As shown in (b, c, d), it can be seen that the product is copper nanoparticles with a particle size of 15 nm and exposed (110) crystal plane.
[0042] Example 4
[0043] In this example, commercial copper powder is used as raw material to prepare copper nanoparticles. The specific steps are as follows:
[0044] Weigh 1 g of commercial copper powder and disperse the weighed copper powder in 200 mL of ultrasonic solution to form a dispersion. The obtained dispersion is ultrasonicated at a power of 400 W for 20 h, and the ultrasonically treated sample is collected. The collected sample is electrochemically reduced at a potential of -1.0 V vs. RHE to obtain copper nanoparticles of corresponding size and crystal surface.
[0045] The SEM image of the commercial copper powder used in this example is as follows: Figure 4 (a) shows the TEM image, HRTEM image and particle size distribution of the prepared copper nanoparticles. Figure 4 As shown in (b, c, d), it can be seen that the product is copper nanoparticles with a particle size of 5 nm and exposed (100) crystal plane.
[0046] Example 5
[0047] In this example, commercial copper powder is used as raw material to prepare copper nanoparticles. The specific steps are as follows:
[0048] Weigh 1 g of commercial copper powder and disperse the weighed copper powder in 200 mL of ultrasonic solution to form a dispersion. The obtained dispersion is ultrasonicated at a power of 400 W for 20 h, and the sample after ultrasonic treatment is collected. The collected sample is electrochemically reduced at a potential of -0.8 V vs. RHE to obtain copper nanoparticles of corresponding size and crystal surface.
[0049] The SEM image of the commercial copper powder used in this example is as follows: Figure 5 (a) shows the TEM image, HRTEM image and particle size distribution of the prepared copper nanoparticles. Figure 5 As shown in (b, c, d), it can be seen that the product is copper nanoparticles with a particle size of 5 nm and exposed (100) crystal plane.
[0050] The performance of the sample in electrocatalytic reduction of CO2 was tested using a flow reactor, in which the prepared copper nanoparticles were used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, the nickel mesh was used as the counter electrode, and the electrolyte was 1 molL -1During the electrochemical test, the chronopotentiometry method was used for testing. The gas products produced by the reaction at different potentials were directly tested by a gas chromatograph connected to the reactor, and the liquid products were subsequently tested by a superconducting nuclear magnetic resonance spectrometer.
[0051] Figure 6 The product efficiency distribution diagram and current diagram of the electrocatalytic reduction of CO2 by the commercial copper powder used in each embodiment are shown in the figure. It can be seen from the figure that in the electrocatalytic reduction of carbon dioxide reaction, the maximum Faraday efficiency of ethylene of the commercial copper powder is only 24%, and the partial current density of ethylene at this efficiency is only 0.023A cm -1 , as the reaction proceeds, the Faradaic efficiency of hydrogen increases dramatically, reaching 58%, eventually leading to catalyst deactivation.
[0052] Figure 7 The product efficiency distribution diagram and current diagram of the electrocatalytic reduction of CO2 by the copper nanoparticles prepared in each embodiment are shown in FIG. 1 . It can be seen that the catalytic performance of copper nanoparticles of different sizes and different crystal faces is different. In terms of selectivity, the maximum Faraday efficiency of ethylene of the copper nanoparticles prepared in Examples 1 to 4 is 50%, 53%, 56% and 79%, respectively, and the corresponding ethylene partial current is 0.30 A cm -1 , 0.49A cm -1 , 0.63A cm -1 and 1.1A cm -1 , from which it can be seen that the catalytic activity of copper nanoparticles is affected by their size and crystal surface.
[0053] During the reaction, the adsorption state of the *CO intermediate on the sample surface will affect its catalytic performance. Figure 8 (ad) are the results related to the adsorption state of *CO intermediates on the surface of each sample. In general, as the sample particle size decreases, the total *CO intermediate adsorption intensity increases. When the sample particle size is 50nm and 25nm, *CO only appears when the test voltage is large. bridge and *CO atop signal peaks, and the intensities of these two signal peaks are relatively weak; when the sample particle size is 15nm, there is *CO at the beginning of the test bridge and *CO atop The signal peak is much higher than that of the samples with particle sizes of 50nm and 25nm. When the sample particle size is 5nm, *CO bridge and *CO atopThe signal peak will also appear when the test is just started, and when the signal peak intensity is high, it can be clearly found that the proportion of the *COatop signal has increased. This also explains why different sample particle sizes will expose different crystal faces during the reaction. Related studies have shown that in the electrocatalytic reduction of carbon dioxide, the type of reaction intermediates may affect the reconstruction process of the catalyst, causing the catalyst to expose different crystal faces. From the above test results, the adsorption intensity of *CO intermediates in samples with a particle size of 50nm and 25nm is generally low during the reaction, and the adsorption intensity of *CO intermediates in samples with a particle size of 15nm is relatively high during the reaction. The adsorption intensity of *CO intermediates in samples with a particle size of 5nm is the highest during the reaction. Different *CO adsorption intensities can adjust the crystal faces exposed by the sample during the reaction. Finally, the difference in the adsorption intensity of *CO intermediates causes samples of different particle sizes to expose different crystal faces during the electrochemical reduction process.
[0054] The above embodiments are typical embodiments of the present invention and are not intended to limit the present invention in any way. For example, the type of copper powder, ultrasonic solution, the ratio of copper powder to ultrasonic solution, ultrasonic conditions, electrochemical reduction parameters, etc. can be further adjusted. Therefore, according to the overall concept of the present invention, adjustments and modifications made by technicians in the relevant technical field to the described process parameters shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the invention or exceed the scope defined by the claims.
Claims
1. A method for preparing copper nanoparticles with controllable size and crystal surface, characterized in that: Commercial copper powder is used as a precursor and converted into copper nanoparticles with controllable size and crystal surface through ultrasonic and electrochemical reduction.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: The commercial copper powder is dispersed in an ultrasonic solution to form a dispersion; the obtained dispersion is subjected to ultrasonic treatment, and the sample after the ultrasonic treatment is collected to obtain copper nanoparticles of a desired size; and then the obtained nanoparticles are electrochemically reduced to obtain copper nanoparticles with a desired crystal surface.
3. The preparation method according to claim 1 or 2, characterized in that: The size of copper nanoparticles is regulated by controlling the ultrasonic time. Copper nanoparticles of different sizes expose different crystal planes after electrochemical reduction, thereby achieving simultaneous control of size and crystal plane.
4. The preparation method according to claim 1 or 2, characterized in that: The ultrasonic power is 400W and the ultrasonic time is 8 to 20 hours.
5. The preparation method according to claim 1 or 2, characterized in that: The potential of the electrochemical reduction is -0.1 to -1.0 V vs. RHE, and the reduction time is 0 to 40 min.
6. The preparation method according to claim 2, characterized in that: The usage ratio of the commercial copper powder to the ultrasonic solution is 0.1-1000 mg:100 mL.
7. Copper nanoparticles with controllable size and crystal surface obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the copper nanoparticles according to claim 7 as a catalyst in the electrocatalytic reduction of carbon dioxide.
9. The use according to claim 8, characterized in that: Used for electrocatalytic reduction of carbon dioxide to produce ethylene.
Citation Information
Patent Citations
Catalyst, electrode and method for preparing ethylene through reduction of carbon dioxide
CN111118601A
Copper nano-electrode with high-index crystal face and preparation method and application thereof
CN111534833A
Copper nanoelectrode rich in twin boundaries and preparation and application thereof
CN113151855A
Preparation method and application of nano-copper catalyst
CN114277398A
Amorphous nano metal copper catalyst as well as preparation method and application thereof
CN116240570A
